Utilization of lignin separated from pulp and paper wastewater for lead removal. (2023) - Khamdahsag, Pummarin; Jarichanon, Thitisuda; Yan, Dickson Y.S.; Grisdanurak, Nurak; Tanboonchuy, Visanu
Abstract: Lignin, which is a major by-product of paper and pulp processing is effectively recovered and repurposed for lead (Pb) removal. This study aimed to extract lignin from real pulp and paper wastewater and then utilized it as an adsorbent for water contaminated-Pb removal. Two types of extracted lignin were compared including 1) lignin precipitated by hydrochloric acid (LP) and 2) lignin separated by the coagulation-flocculation process using iron(III) trimesate, a type of the iron-based metal–organic framework, (LPF). They were characterized using a scanning electron microscope (SEM), nitrogen adsorption–desorption, Fourier transform infrared (FTIR) spectroscopy, X-ray fluorescence (XRF), and thermogravimetric analysis (TGA). LPF showed amorphous characteristics, surface area, and porous increased, and iron oxide appeared compared to LP. Batch experiment results revealed that LPF decreased Pb contamination in water by approximately 65 % in 60 min. Adsorption kinetics had a better fit to the pseudo-second-order model. The adsorption process occurred spontaneously and was endothermic, following the physisorption mechanism. The adsorption isotherm model fitted the Freundlich isotherm well, while parameter (n) as 2.015 implied favorable adsorption. The outcomes of the research might open the door to the creation of lignin-based adsorbents for the elimination of Pb in wastewater.